2020
DOI: 10.1071/fp19082
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of genes involved in galactolipids and sulfolipids metabolism in maize and Arabidopsis and their differential responses to phosphate deficiency

Abstract: Galactolipids (MGDG and DGDG) and sulfolipids (SQDG) are key components of plastidic membranes, and play important roles in plant development and photosynthesis. In this study, the whole families of MGD, DGD and SQD were identified in maize genome, and were designated as ZmMGD1-3, ZmDGD1-5 and ZmSQD1-5 respectively. Based on the phylogenetic analyses, maize and Arabidopsis MGDs, DGDs and SQDs were clearly divided into two major categories (Type A and Type B) along with their orthologous genes from other plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In this study, a significant decrease of MGDG and a slight increase of DGDG was observed, resulting in a large reduction in the MGDG/DGDG ratio in maize seedlings under cold stress. MGD catalyzes the galactose transfer from UDP-galactose to DAG framework to form MGDG, and then the second galactose is diverted from UDP-galactose to MGDG by DGD for the final formation of DGDG (Wang et al, 2020). In our transcriptomic data, the expression of two maize DGDs were up-regulated, and the most apparent one had a Log2FC of 2.56.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, a significant decrease of MGDG and a slight increase of DGDG was observed, resulting in a large reduction in the MGDG/DGDG ratio in maize seedlings under cold stress. MGD catalyzes the galactose transfer from UDP-galactose to DAG framework to form MGDG, and then the second galactose is diverted from UDP-galactose to MGDG by DGD for the final formation of DGDG (Wang et al, 2020). In our transcriptomic data, the expression of two maize DGDs were up-regulated, and the most apparent one had a Log2FC of 2.56.…”
Section: Discussionmentioning
confidence: 60%
“…This membrane remodeling occurs in a process dependent on the activation of monogalactosyldiacylglycerol synthase induced by a low Pi level. Studies have already observed this pattern in leaves and roots with different plant species under Pi depletion, including Sesamum indicum , Zea mays , and Arabidopsis thaliana [ 42 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 88%
“…Phosphorus deficiency in canga can be related to the formation of complexes between P and iron oxides, limiting plant uptake availability [ 41 ]. Roots from plants sampled in canga showed more proteins related to P depletion, such as monogalactosyldiacylglycerol synthase 2, phospholipase, alcohol dehydrogenase, extracellular purple acid phosphatases, and antioxidant system proteins such as catalases and monodehydroascorbate reductases [ 42 , 43 , 44 ]. During Pi deprivation, glycolipids are transferred to extraplastid membranes, where they replace degraded phospholipids to meet the need for Pi essential for various biological processes in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane remodeling occurs in a process dependent on the activation of monogalactosyldiacylglycerol synthase induced by a low Pi level. Studies have already observed this pattern in leaves and roots with different plant species under Pi depletion, including Sesamum indicum, Zea mays, and Arabidopsis thaliana [46,49,50].…”
Section: Proteins Involved In the Response To P-starvationmentioning
confidence: 71%
“…Phosphorus deficiency in canga can be related to the formation of complexes between P and iron oxides, limiting plant uptake availability [45]. Roots from plants sampled in canga showed more proteins related to P depletion, such as monogalactosyldiacylglycerol synthase 2, phospholipase, alcohol dehydrogenase, extracellular purple acid phosphatases, and antioxidant system proteins such as catalases and monodehydroascorbate reductases [46][47][48]. During Pi deprivation, glycolipids are transferred to extraplastid membranes, where they replace degraded phospholipids to meet the need for Pi essential for various biological processes in the cell.…”
Section: Proteins Involved In the Response To P-starvationmentioning
confidence: 99%